VISUALIZING EDUCATIONAL REFORM: A COMPARATIVE ANALYSIS OF CM RISE AND OTHER GOVERNMENT SCHOOLS IN MADHYA PRADESH - Shrivastav, Mrs. Akhilesh; Pandey, R.P. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Education is a fundamental pillar of national development and social equity. In Madhya Pradesh, the CM Rise Schools initiative represents one of the most ambitious school reform programmes in recent Indian education history, designed to transform selected government schools into modern, technology-enabled centres of excellence. This study undertakes a comparative analysis of CM Rise Schools and other government schools in Madhya Pradesh, examining their practices, policies, and educational outcomes across nine key dimensions: teacher adequacy and qualification, academic achievement, professional development programmes, government funding, infrastructure facilities, co-curricular activities, teaching–learning processes, student discipline strategies, and educational policy frameworks. The study employed a comparative and descriptive survey research design. A stratified random sample of 20 schools—10 CM Rise Schools and 10 other Government Schools—was selected from the Ujjain Division of Madhya Pradesh. Data were collected from 20 principals, 200 teachers, 300 parents, and 2938 Class 10 students through structured questionnaires, observation checklists, and document analysis. The percentage method was used for data analysis. Findings reveal that CM Rise Schools demonstrate consistently superior performance across infrastructure, professional development, technology integration, teaching–learning strategies, and student discipline. Academic achievement data from 2022–23 and 2023–24 show CM Rise Schools achieving higher percentages of students scoring above 60% in Class 10 board examinations. However, disparities in teacher deployment, staffing vacancies, and equity concerns challenge the uniformity of outcomes across all CM Rise Schools. The study concludes that while CM Rise Schools represent a commendable reform model, the long-term success of public education reform in Madhya Pradesh depends on systematically scaling the best practices of CM Rise to the broader network of government schools.